Relationship between general attitude towards nature, religion, custom, science and technological progress and attitude towards modern biotechnology - Latifah Amin,; Jamaluddin Md. Jahi,; Abd Rahim Md Nor,; Mohamed Osman,; Nor Muhammad Mahadi, (Environmental Management Society, Malaysia, 2005)
Modern biotechnology has been classified as a complex emerging issue that exhibits high salience combined with limited knowledge on part of the public. It has been suggested by social scientists that any complex object may be located in a variety of general classes where its evaluation may be strongly affected by extraneous concerns. The purpose of this paper is to analyse the relationship between several general classes of attitudes and attitude towards genetically modified soybean as an example of modern biotechnology product available in Malaysia. A survey was carried out on 991 respondents from various interest groups in the Klang Valley region. Results of the survey have confirmed that attitude towards complex issues such as biotechnology should be seen as a multi-faceted/multidimensional process. The most important factors predicting encouragement of GM soybean are the specific application-linked perceptions about the benefits, acceptance of risk and moral concern while risk and familiarity are significant predictors of benefit and risk acceptance. Attitude towards GM soybean is also predicted by several general classes of attitude such as general promise and concern of biotechnology, technology optimism, nature/materialistic value, predisposition towards science and technology, attachment to religion and custom. Researchers, policy-makers and industries interested in developing and marketing GM products in Malaysia should consider the various factors mentioned in this study in order to gain public approval